(untitled) (Comparative & International Education Series, 2022)
The parade ended sooner than I had expected. It was still early, and I didn’t have the slightest idea about how and what I should fill the rest of the day with. Suddenly, time had become my enemy, and I didn’t know how to beg for its mercy, to make it pass faster and especially not to let it poison every moment it was offering to me, which was passing as if it were a whole year. I joined the group of people who knew exactly that one of the restaurants in the university campus was offering food for free, so why shouldn’t we all go there and take advantage of this? I didn’t feel like doing it, but the perspective of loneliness, sister with depression, was really scaring me, so I followed them. They were noisy and funny, obviously feeling good, but my mind didn’t have the strength to play their game or to draw their attention to something more serious. Only five minutes later, I ran away, aware that I was to face the danger.